Evaluation of Silica Uptake from Foliar-Applied Silicon Nanoparticles in Melon (Cucumis melo L.) under Soilless Culture - Badrieh, Haian Amin; Widodo, Winarso Drajad; Susila, Anas Dinurrohman; Suwarno, Willy Bayuardi (Department of Agronomy and Horticulture, IPB University, 2021)
Melon (Cucumis melo L.) is a fruit commodity that gets a great interest to be developed in Indonesia and has a high nutritional value. However, the fungal infection and pathogens in melon cultivation are considered significant problems that are difficult to manage. Therefore, efforts are needed to improve the productivity and quality of melon and prevent pest and disease attacks. One mineral nutrient that is assumed to enhance plant resistance and increase the quality and production of melon is silica. The purpose of the research was to evaluate silica absorption from foliar-applied silicon nanoparticles in melon under soilless culture and improve melon fruit's growth and quality by applying silica fertilizer. The experimental design used was a split-plot randomized complete block design 3 x 2 factorial pattern with four replicates. The main plot factor is silica fertilizer (Novelgro, water-soluble), consisting of three silica concentrations of 0.67; 1.33 ppm, and control. The spray volume of each treatment was 160 ml per plant with seven days' intervals and a frequency of three times. The subplot factor is melon varieties consisting of “Alisha” and “Glamour”. The findings showed that silica fertilizer significantly increased the plant height, stem diameter, internode length, total number of hermaphrodite flowers, number of hermaphrodite flowers that are swelling, while decreased the fruit moisture content and gave the best average fruit position. Instead, The “Glamour” variety gave the best response to plant growth and fruit quality. Moreover, the melon plant could absorb silica in the low category (<1% Si). The highest silica contents were found in the “Alisha” cultivar leaves and the “Glamour” cultivar's rinds treated with the silica concentration of 1.33 ppm as much as 0.34% and 0.30%, respectively.